Intermittent Theta Burst Stimulation Over Ventral Premotor Cortex or Inferior Parietal Lobule Does Not Enhance the Rubber Hand Illusion - Mioli, Alessandro; D’Alonzo, Marco; Pellegrino, Giovanni; Formica, Domenico; Di Pino, Giovanni (Frontiers in Neuroscience, 2018)
An enhanced sense of prosthesis ownership may be the key for higher amputees’ quality of life. In this study in 28 healthy subjects, neuronavigated intermittent Theta Burst Stimulation (iTBS) delivered over the right ventral premotor cortex or inferior parietal lobule has been tested, compared to sham stimulation, to enhance embodiment in the rubber hand illusion paradigm. Neuromodulation of both areas did not result in an enhancement of embodiment, as assessed by the results collected from a self-evaluation questionnaire for the extent of self-attribution of the rubber hand and proprioceptive drift. In all cases, the difference between synchronous and asynchronous stroking confirms the successful induction of the illusion. It may be speculated that the low consistency of iTBS over brain regions other than primary motor cortex may account for the absence of effect, suggesting to test other neuromodulating techniques, acting on cortical networks different from the ones sensitive to iTBS to enhance artificial hand embodiment.